DETERMINATION OF MICROPARAMETERS OF CHALCOGENIDE THIN CURTAINS (Scientific journal of the Fergana State University, 2024)
Anomalous photomagnetic effect is mainly observed in thin layers of AFK effect, which generate high photovoltage and photomagnetic voltage by the p–n mechanism. It was known that a typical representative of such layers is an alloy of cadmium tellurium and antimony and selenium. It has now been found that AFK-layers can also be obtained from cadmium, mercury and tellurium alloys (KRT). The formation mechanism of anomalous high photovoltage in AFK-layers obtained from this alloy is photovoltaic (p-n-transition). Taking this into account, anomalous photomagnetic voltage generation was also found in cadmium, mercury and tellurium (CdHg)Te, AFK-layers.